Monitoring Climate Changes By Geographical Information Systems (GIS): A Case Study of Izmir City - Anıl Can Birdal; Engin Korkmaz; Gökhan Erşen; Tarık Türk; Rutkay Atun (Doğal Afetler ve Çevre Dergisi)
Climate is one of the most important factors that enable the existence of life on Earth. The climate has been studied by many scientists throughout the history for its influence on all living and non-living beings. Researchers have used climatological parameters (temperature, humidity, rainfall, sunshine duration, evapotranspiration etc.) with different approaches and created a variety of methods. When putting these classifications into consideration, they have taken different criteria into account and have produced different classification. Some of these formulas are short and simple, some are very long and complex. Using these formulas, researchers have determined different climatic types suited to different regions. In this study, two separate climate classification methods were used (Erinç and De Martonne). Meteorological data ranging from 1980 to 2011 were examined periodically and arranged according to determined classification methods. The data were processed in accordance with De Martonne and Erinç classification formulas by GIS and the climate change of İzmir province has been revealed between 1980-1989 and 2006-2011 time periods.